The Power of the Media on Peace and Reconciliation Processes: Representing Former Enemy Groups as Moral versus Immoral Matters. (April 2021) - Janković, Ana; Čehajić-Clancy, Sabina
The efforts of peace-building and reconciliation between historical enemies are faced with many structural and psychological obstacles. Scholars have identified mechanisms that can induce improvements in psychological aspects of intergroup relations, such as intergroup contact. However, establishing direct contact with everyone is impossible. Therefore, the mass media represents an important source through which groups learn about each other. Numerous studies have shown that stereotypical and often negative portrayals of specific social groups through the media produce or reinforce negative intergroup outcomes. In this research, the authors report results from an experimental study conducted in a post-conflict society of Bosnia and Herzegovina ( N  = 119). It examined the effects of stereotypical and counter-stereotypical representations of former enemy groups (Bosniaks) through the media on intergroup behavior (reported by Bosnian Serbs). More specifically, in this research the authors explored the effects of representing out-group individuals as immoral (the stereotypical condition) and moral (the counter-stereotypical condition) on specific behavioral tendencies toward the historical enemy group. The results indicate that exposure to primarily moral information about the out-group target facilitated important positive intergroup outcomes. This study extends the literature and research on moral exemplars by demonstrating the effects on relevant intergroup outcomes whilst utilizing current (vs. historical) moral exemplar stories.